Enhanced capacitance retention in a supercapacitor made of carbon from sugarcane bagasse by hydrothermal pretreatment - Wahid, Malik; Puthusseri, Dhanya; Phase, Deodatta; Ogale, Satishchandra (Energy & Fuels, 2014)
A unique morphology-controlling protocol involving hydrothermal preprocessing before pyrolysis is presented to convert cellulosic waste in the form of sugarcane bagasse into three-dimensional (3D) interconnected, conducting, and high surface area carbon nanochannels. The large buffer spaces in such a porous carbon sample yield impressive electrochemical capacitance (C-sp) of 280 F/g at a current density of 1 A/g (and 275 F/g at 5 mV/s), with 72% retention even at a very high current density of 20 A/g. In contrast, the non-hydrothermally treated sample exhibits a C-sp value of 180 F/g at 1 A/g and only 52% retention at 20 A/g. The much better performance of the hydrothermally preprocessed bagasse-derived carbon (BHAC) can be ascribed to the solvent retention inside the buffer spaces created, negating the diffusional limitations of pore inaccessibility at higher scan rates. The BHAC has a high surface area of 1260 m(2)/g with a fairly good (11 wt %) concentration of oxygen functionality. The material renders a good energy density of Wh/kg at a power density of 3.5 kW/kg and shows good cyclability of 90% after 1000 charge/discharge cycles.